2000
DOI: 10.1088/0268-1242/15/8/310
|View full text |Cite
|
Sign up to set email alerts
|

Defect monitoring using scanning photoluminescence spectroscopy in multicrystalline silicon wafers

Abstract: Scanning photoluminescence (PL) spectroscopy was performed on as-grown and processed multicrystalline silicon (mc-Si) wafers to investigate the defect distribution affecting the efficiency of solar cells. In highly inhomogeneous mc-Si prepared by (i) edge-defined film-fed growth or (ii) a block-casting technique, regions of a wafer with enhanced recombination activity and reduced minority carrier lifetime exhibit an intensive 'defect' PL band at room temperature with the maximum at about 0.8 eV. By comparing P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
51
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 27 publications
7
51
0
Order By: Relevance
“…Near liquid nitrogen temperature, the D4 peak was reported to be higher than the D3 peak in [7] and [11]. However, the opposite observation was presented in other works [8], [23].…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…Near liquid nitrogen temperature, the D4 peak was reported to be higher than the D3 peak in [7] and [11]. However, the opposite observation was presented in other works [8], [23].…”
mentioning
confidence: 69%
“…Some reported spectra in which the D2 line was a less-significant peak embedded on the high-energy side of the intense D1 line [7], [11], [12], [14]. Others reported spectra with the D2 line present, but with D1 absent [9], [13].…”
mentioning
confidence: 99%
“…36͒ is most likely to be related to thermal donors or oxygen clusters bound to dislocations or trapped in the strain field of dislocations. In a more detailed study, Ostapenko et al 37 reported a very good qualitative correlation of a reduced car- rier lifetime, strong defect photoluminescence at around 0.8 eV, decreased band-to-band photoluminescence, and enhanced dislocation density.…”
Section: B Light Emission From Forward-biased P-n Junctionsmentioning
confidence: 97%
“…Recently Mchedlidze associates screw dislocations with a small twist angle to the D-lines and the edge dislocations to non radiative recombination. 13 Investigation of DRL is mainly performed by laboratory-based spectroscopic point mapping methods, such as described by Mudryi et al 14 and Ostapenkoet al 8 Recently single band methods using band pass filters on InGaAs cameras have been reported by Mankovics et al 15 and Schmid et al 16 Also hyperspectral technologies have been applied by Peloso et al, 17 as well as by Olsen&Flo 18 and Burud et al 19 The advantage of using hyperspectral imaging is that the entire spectrum is acquired at each point. Instead of selecting a priori regions for detailed studies with e.g.…”
Section: B D-linesmentioning
confidence: 99%